NETWORKS THAT COUNT. SYSTEMATIC REVIEW ON SUBJECTIVE WELL-BEING AND PERCEIVED SOCIAL SUPPORT IN ADOLESCENCE - Noelia Laino (Revista Científica Arbitrada de la Fundación MenteClara, 2023)
The following article presents a literature review around the concepts of subjective well-being and perceived social support. The search was carried out in Google Scholar and it was considered that they were works presented in journals of academic prestige. In addition, some research was investigated that established relationships between these concepts in adolescence. The work was carried out within the framework of an evaluative proposal for the subject Health Psychology, whose axis focuses on the approach of concepts of Positive Psychology. In this sense, it is of interest to note that this branch of psychology proposes the study of those factors that promote and enhance optimal psychological functioning. Conceptual definitions were contrasted around subjective well-being and perceived social support, outlining possible psychometric measurement instruments for both concepts. Finally, there was a difficulty in finding articles that related both constructs around this population, raising some questions regarding the adequacy of the instruments.